Analisis Kesulitan Siswa dalam Menyelesaikan Soal Operasi Bilangan Pecahan pada Siswa SMP - Azis Azis; Maya Nurlita; Zulkifran Zulkifran (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2022)
The purpose of this study was to find out the difficulties experienced by students in solving fractional operations problems in addition and subtraction of fractions. This research was carried out at SMP Negeri 6 Lasalimu Selatan, Lasalimu Selatan District, Buton Regency with the sample of this research being all class VII students of SMP Negeri 6 Lasalimu Selatan, totaling 32 students using a descriptive method whose main concern was the results of students' mathematics tests on the subject of fractional operations. From the results of the analysis and discussion in this study, it can be concluded that the difficulties faced by the seventh grade students of SMP Negeri 6 Lasalimu Selatan in solving fractional operations problems are the difficulties of concepts, principles, and skills. Concept difficulty with 17 errors and a large percentage of about 13.08%, principle difficulty with 24 errors and a large percentage of about 18.46%, and skill difficulty with 59 errors and a large percentage of about 45.38%. Therefore, it is necessary to emphasize to students about the concepts, principles, and skills used in fractional arithmetic operations (especially the operation of adding and subtracting fractions) by re-explaining problems that students do not understand and giving relevant assignments with these difficulties.